Negative income shocks and the support of environmental policies: Insights from the COVID-19 pandemic - Andreas Löschel; Michael Price; Laura Razzolini; Madeline Werthschulte (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2020)
This study explores whether negative income shocks from the COVID-19 pandemic affect the demand for environmental policy. By running a survey in Germany in May 2020, we show that there is a large and negative correlation between the COVID-19 income shocks and the willingness to support green policies. Importantly, this relation is separate from the effect of long-run income. Building on this first evidence, our study provides directions for future valuation studies. Specifically, our results provide a proof of concept that welfare analyses based on willingness-to-pay estimates to assess the benefit of an environmental good or the cost of an environmental damage may be downward biased if temporary changes in income are not considered.
Keywords: Q51; Q58; D61; 330; COVID-19; Environmental policy; Income shock; Welfare analysis; Willingness topay